Oleuropein aglycone and hydroxytyrosol interfere differently with toxic Aβ1-42 aggregation. (July 2019) - Leri, Manuela; Natalello, Antonino; Bruzzone, Elena; Stefani, Massimo; Bucciantini, Monica
Abstract: Oleuropein aglycone (OleA), the most abundant polyphenol in extra virgin olive oil (EVOO), and Hydroxythyrosol (HT), the OleA main metabolite, have attracted our interest due to their multitarget effects, including the interference with amyloid aggregation path. However, the mechanistic details of their anti-amyloid effect are not known yet. We report here a broad biophysical approach and cell biology techniques that enabled us to characterize the different molecular mechanisms by which OleA and HT modulate the Aβ1–42 fibrillation, a main histopathological feature of Alzheimer's disease (AD). In particular, OleA prevents the growth of toxic Aβ1–42 oligomers and blocks their successive growth into mature fibrils following its interaction with the peptide N-terminus, while HT speeds up harmless fibril formation. Our data demonstrate that, by stabilizing oligomers and fibrils, both polyphenols reduce their seeding activity and aggregate/membrane interaction on human neuroblastoma SH-SY5Y cells. These findings highlight the great potential of EVOO polyphenols and offer the possibility to validate and to optimize their use for possible AD prevention and therapy. Graphical abstract: Image 1 Highlights: OleA interacts with the N-terminus of Aβ1-42 peptide. OleA stabilizes Aβ1-42 non-toxic oligomeric forms. HT increases harmless Aβ1-42 fibrils formation. OleA and HT modulate the seeding activity of Aβ1-42 fibrils. OleA and HT reduce the amyloid cytotoxicity including Ca 2+ flux and oxidative stress.